FORMATION OF THE PHYSICAL AND SPORTS ENVIRONMENT OF THE UNIVERSITY AS A CONDITION FOR REGULAR PARTICIPATION OF STUDENTS AND TEACHERS OF VI-XI STAGES IN IMPLEMENTATION OF STANDARDS OF THE VFSK GTO - Bobkov, V.V.; Ryzhkova, L.G.; Lazarev, I.V.; Tatarova, S.Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of holding multi-day GTO festivals and organizing academic and independent physical education classes with students, in accordance with the types of tests of the VFSK GTO of the VI stage. Methods and structure of the study. The scientific work was attended by students and teachers of the Russian State University for the Humanities in the amount of 1363 participants, among whom were representatives of male and female, belonging to the VI-X stages of the VFSK GTO by age. Physical culture lessons were based on the principle of circular training based on the method of continuous exercise. All types of tests were divided into three groups: in the hall, at the stadium, applied. Starting from April and until the end of the semester (end of May), the university held the GTO Festival, based on the results of which a detailed analysis of the quantitative and qualitative indicators of the performance of the GTO tests was carried out. Results and conclusions. Most of the students (82%) and the teaching staff of the Department of Physical Education (100%) took part in the GTO Festival at the Russian State University for the Humanities, of which 67% of the participants improved their performance in tests during repeated testing, and 23% met the standards for gold, silver and bronze marks of Excellence. Holding a multi-day GTO Festival allows solving a very important problem related to the possibility of re-executing test tests. When holding the GTO Festival at the university, students have the opportunity to independently choose the most suitable moment for themselves to complete the tests. The close interaction of the departments of physical education of universities and the Testing Centers of the GTO “MOSGORSPORT” of Moskomsport allows solving the problem of attracting more students to the events of the VFSK GTO with the assignment of distinctions, as well as promoting a healthy lifestyle among the youth.